2015
DOI: 10.1136/jnnp-2015-311680
|View full text |Cite
|
Sign up to set email alerts
|

Constipation preceding Parkinson's disease: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis demonstrates that people with constipation are at a higher risk of developing Parkinson's disease compared with those without and that constipation can predate Parkinson's diagnosis by over a decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 24 publications
3
132
0
Order By: Relevance
“…This hypothesis is supported by the observation that truncal vagotomy is associated with a lower risk of PD . Also, several gastrointestinal disorders, such as constipation, irritable bowel syndrome (IBS), and inflammatory bowel disease are associated with a higher risk of PD. Lewy‐type pathology has been detected in the gastrointestinal tract up to 20 years prior to PD diagnosis, and prominent denervation of the gut in prodromal and established PD has been demonstrated …”
mentioning
confidence: 89%
“…This hypothesis is supported by the observation that truncal vagotomy is associated with a lower risk of PD . Also, several gastrointestinal disorders, such as constipation, irritable bowel syndrome (IBS), and inflammatory bowel disease are associated with a higher risk of PD. Lewy‐type pathology has been detected in the gastrointestinal tract up to 20 years prior to PD diagnosis, and prominent denervation of the gut in prodromal and established PD has been demonstrated …”
mentioning
confidence: 89%
“…82 Meta-analyses reveal that constipation is more than 2 times common in people who develop PD compared to normal people, 83 and individuals with constipation have 2 times the chance to have PD within 10 years of their evaluation. 84 The time duration over which constipation indicates the development of PD is remarkable. After prospective and retrospective studies, it has been found that constipation becomes apparent at an average of 15.6-24.0 years before PD is diagnosed.…”
Section: Constipationmentioning
confidence: 99%
“…For this reason, much attention has been focused on the GI tract, which is heavily burdened by Lewy pathology (13) and commonly expresses symptoms including dysphagia, bloating and constipation (14). Of these, constipation has been reported to manifest as early as 10 years prior to motor symptoms (15). Curiously, accumulation of α-synuclein can occur in the gut up to 10 years prior to diagnosis (16).…”
Section: Introductionmentioning
confidence: 99%